2014
DOI: 10.1037/a0037067
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aging on sustained attention ability: An ERP study.

Abstract: The aim of this study was to investigate the effects of aging on inhibitory processes and attentional resources in a long-lasting Go/No-Go sustained attention task using the event-related potential (ERP) technique. In line with recent studies, our results showed that older adults were able to maintain sustained attention performance throughout the duration of the task, whereas younger subjects exhibited a vigilance decrement. Regarding ERP results, older adults had larger P2 and Go-P3 amplitudes, components re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 84 publications
(134 reference statements)
11
30
1
Order By: Relevance
“…Lastly, replicating previous findings on the age-related effect of P2 [37, 65, 66], our regression analysis results also showed that age predicted P2 amplitudes at frontal sites. More interestingly, our results delineated the effect of age from the effect of mindfulness on P2 amplitudes: age mainly affected positive (compared to neutral) stimuli (Pos-Neu) at frontal locations, while mindfulness influenced the difference between positive and negative stimuli (Pos-Neg) at frontocentral sites (less anterior).…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, replicating previous findings on the age-related effect of P2 [37, 65, 66], our regression analysis results also showed that age predicted P2 amplitudes at frontal sites. More interestingly, our results delineated the effect of age from the effect of mindfulness on P2 amplitudes: age mainly affected positive (compared to neutral) stimuli (Pos-Neu) at frontal locations, while mindfulness influenced the difference between positive and negative stimuli (Pos-Neg) at frontocentral sites (less anterior).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the enhanced and topographically-different P1 in the Older group might suggest enhanced prestimulus focus on the task, which would be compatible with the investment of greater effort. These interpretations are consistent with the typical view that older adults employ compensatory mechanisms in order to perform satisfactorily (e.g., Friedman et al, 1997;Hong et al, 2014;Hsieh and Fang, 2012;Staub et al, 2014;Vallesi, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…The frontal negativity of the classic SW has also been reported to be absent in an older group (Pfefferbaum et al, 1980). This type of topographic finding has been interpreted increasingly as evidence for compensatory frontal activity in older compared with younger subjects, used to maintain relatively high performance levels (e.g., Hong et al, 2014;Hsieh and Fang, 2012;Staub et al, 2014;Vallesi, 2011) in the context of reductions in frontal brain volume (Driscoll et al, 2009;Raz et al, 2005).…”
Section: Fig 1 About Herementioning
confidence: 91%
“…These authors viewed this age effect as a deficit in the capacity to withdraw processing resources from irrelevant stimuli at early stages of perceptual analysis, suggesting that P2 amplitude over occipital sites was rather related to bottom-up attentional processing. Regarding the frontally distributed P2, previous studies have already evidenced age-related increases in frontal P2 amplitudes (Amenedo & Diaz, 1999;Anderer, Semlitsch, & Saletu, 1996;Getzmann, Gajewski, & Falkenstein, 2013;Staub et al, 2014b), a component that has been conceptualized as a marker of the activation of top-down attentional control over the processing of task-relevant stimuli (Luck & Hillyard, 1994). Thus, our results suggest that compared to younger adults, older participants allocated more attentional resources to the task at hand, irrespective of its nature.…”
Section: Discussioncontrasting
confidence: 50%
“…In other words, discrepancies regarding the effect of age on sustained attention performance in each approach could be explained by a differential use of automatic and controlled processes as a function of age in a situation of sustained attention. For example, recent results showed that in a long-lasting Go/No-Go sustained attention task, older adults deployed increased levels of attentional control relative to younger subjects (Staub, Doignon-Camus, Bacon, & Bonnefond, 2014b). In order to put this possibility to the test, we employed in the current study two versions of the SART which only differed in their response mode -a TFT version, which mostly relies on automatic processes, and the regular Go/No-Go version, which mostly relies on controlled processes, together with the event-related potentials (ERP) technique, allowing us to examine, in a time on task perspective, the automatic or controlled nature of processing adopted by each group in these tasks.…”
mentioning
confidence: 97%